Endocrine Hypertension - a Multifaceted Disease - Tudurachi Bogdan-Sorin; Țăpoi Laura; Şalaru Delia Lidia; Benchea Laura Cătălina; Pleșoianu Carmen Elena; Sascău Radu Andy; Stǎtescu Cristian (Sciendo, 2022)
Secondary hypertension with an endocrine-associated condition-pheochromocytoma, primary aldosteronism (PA), Cushing's syndrome, acromegaly, congenital adrenal hyperplasia, hypo- and hyperthyroidism, renin-secreting tumors, and hyperparathyroidism- represents a small but heterogeneous group of potentially reversible forms of hypertension. High clinical suspicion is the cornerstone of diagnosing these different patterns of often severe and refractory hypertension.